1998
DOI: 10.1023/a:1007941622680
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The simian virus 40 (SV40) large T antigen is a 708 amino-acid protein possessing multiple biochemical activities that play distinct roles in productive infection or virus-induced cell transformation. The carboxy-terminal portion of T antigen includes a domain that carries the nucleotide binding and ATPase activities of the protein, as well as sequences required for T antigen to associate with the cellular tumor suppressor p53. Consequently this domain functions both in viral DNA replication and cellular trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…LT-Ag proteins encoded by SV40, BK virus, and JC virus have been shown to directly bind to p53 (15,(53)(54)(55)(56)(57)(58), whereas mouse polyomavirus LT-Ag does not bind p53 or inhibit p53-dependent transcription (59). To investigate whether the observed coprecipitation of MCPyV LT antigen with p53 is due to direct or indirect binding, we performed FACS-FRET experiments with living cells, as recently described (44), using different cell lines that ectopically express MCPyV LT or SV40 LT proteins and p53 as YFP or CFP fusion proteins.…”
Section: Resultsmentioning
confidence: 99%
“…LT-Ag proteins encoded by SV40, BK virus, and JC virus have been shown to directly bind to p53 (15,(53)(54)(55)(56)(57)(58), whereas mouse polyomavirus LT-Ag does not bind p53 or inhibit p53-dependent transcription (59). To investigate whether the observed coprecipitation of MCPyV LT antigen with p53 is due to direct or indirect binding, we performed FACS-FRET experiments with living cells, as recently described (44), using different cell lines that ectopically express MCPyV LT or SV40 LT proteins and p53 as YFP or CFP fusion proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, free p53 has been reported in nuclear matrix fractions of SV40-transformed cells (Deppert and Haug, 1986). Mutants of SV40 large T that fail to interact with p53 also fail to bind the nuclear matrix (Deppert et al, 1989) and are transformation defective (Peden et al, 1989(Peden et al, , 1998. This raises the possibility that the sub-nuclear positioning of large T by p53 contributes towards the transforming potential of SV40 large T. In this context it is interesting to note that the association of large T with p300/CPB is also linked with its binding capacity for p53 and it has been suggested that p53 may mediate large T interaction with p300/CBP (Avantaggiati et al, 1996;Eckner et al, 1996;Lill et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In infected cells, viral protein (SV40 large T antigen [T-Ag]) binds p53 and inhibits p53-dependent transcription, resulting in accumulation of inactivated p53 protein [ 3 , 4 ]. Inhibition of p53 by large T-Ag is closely linked to the ability of the SV40 virus to induce tumorigenic transformation; SV40 mutants, which are defective in inhibition of p53, are also defective in cellular immortalization and transformation [ 5 , 6 ].…”
Section: Historical Perspective Of Microbial Inhibition Of P53mentioning
confidence: 99%